PENGARUH PENGUNGKAPAN ENVIRONMENTAL, SOCIAL AND GOVERNANCE (ESG) TERHADAP NILAI PERUSAHAAN PADA PERUSAHAAN AGROINDUSTRI DI INDONESIA - Ilma, Lusyana Nur; Wahyuni, Nining Ika (Pusat Penelitian dan Pengabdian kepada Masyarakat Sekolah Tinggi Ilmu Ekonomi Trisakti, 2025)
This study aims to analyze the influence of Environmental, Social, and Governance (ESG) on company value in the agro-industrial sector in Indonesia. The background of this study is based on the increasing trend of investor attention to aspects reflected in ESG. Company value is measured using the Price to Book Value (PBV) ratio, while the ESG score is calculated based on the GRI Standards 2021. The method used in this study is a quantitative approach with multiple linear regression analysis techniques. The sample consists of 24 agro-industrial companies listed on the Indonesia Stock Exchange during the 2022–2024 period with a total of 72 observations. The control variables used in this study include Return on Assets (ROA), company size, and Debt to Equity Ratio (DER). The results of the study indicate that ESG closure has a positive and significant effect on company value, which supports the theoretical signal that ESG is a positive signal of long-term commitment to the sustainability of the company. In addition, the DER variable also has a significant positive effect, while ROA and company size have a significant negative effect on company value. The coefficient of determination value of 0.298 indicates that the model can explain about 29.8% of the variation in company value. This finding shows that although ESG is not the only factor, it has an important contribution in shaping market perception and increasing the value of agro-industry companies in Indonesia.